2023
DOI: 10.1136/bmjopen-2023-071867
|View full text |Cite
|
Sign up to set email alerts
|

Burden of opioid toxicity death in the fentanyl-dominant era for people who experience incarceration in Ontario, Canada, 2015–2020: a whole population retrospective cohort study

Abstract: ObjectivesTo describe mortality due to opioid toxicity among people who experienced incarceration in Ontario between 2015 and 2020, during the fentanyl-dominant era.DesignIn this retrospective cohort study, we linked Ontario coronial data on opioid toxicity deaths between 2015 and 2020 with correctional data for adults incarcerated in Ontario provincial correctional facilities.SettingOntario, Canada.ParticipantsWhole population data.Main outcomes and measuresThe primary outcome was opioid toxicity death and th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
2
5
0
Order By: Relevance
“…We found significant differences in the increase in risk during the COVID-19 period between people exposed and not exposed to incarceration, as well as by sex. Consistent with pre-pandemic studies [ 1 , 3 , 4 , 8 ], females exposed to incarceration continued to be at greater risk of death by opioid toxicity compared to females who were not exposed to incarceration. However, males exposed to incarceration were most significantly impacted by COVID-19 in terms of the increased risk of death.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…We found significant differences in the increase in risk during the COVID-19 period between people exposed and not exposed to incarceration, as well as by sex. Consistent with pre-pandemic studies [ 1 , 3 , 4 , 8 ], females exposed to incarceration continued to be at greater risk of death by opioid toxicity compared to females who were not exposed to incarceration. However, males exposed to incarceration were most significantly impacted by COVID-19 in terms of the increased risk of death.…”
Section: Discussionsupporting
confidence: 70%
“…The drug toxicity crisis has worsened over the past two decades and has disproportionately impacted people who experience incarceration [ 7 , 8 , 13 ]. Since 2016, the crisis has been largely fuelled by illicitly manufactured fentanyl and fentanyl analogues and an unregulated drug supply which is unpredictable in composition [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Because both of MADOC’s female-population prisons implemented buprenorphine in April 2019, the entire female population gained access from the start, compared with only 2 out of the 11 male-population MADOC prisons. Additionally, the female sample in MADOC may have had a higher prevalence of OUD and therein a greater proportion who stood to gain from access to buprenorphine, which was evidenced by their higher postrelease overdose rates (in this study and others) and would mirror prevalence estimates in national carceral samples . Furthermore, the female MADOC sample includes some county jail populations, which typically have a higher prevalence of substance use disorders than prison populations…”
Section: Discussionmentioning
confidence: 65%
“…We suspect that the provision of MOUD while incarcerated drove the substantial increase in postrelease buprenorphine receipt. Our data source lacked information on treatment received in prison, but a published MADOC report 49 with data from October through December 2019 (a few months after implementation) showed that a mean of 76.7 male patients and 53.3 female patients each month received buprenorphine in the pilot facilities-a treatment volume large enough to translate into the observed postrelease treatment increases. Nevertheless, additional mechanisms (ie, spillover effects) may have also played important roles.…”
Section: Discussionmentioning
confidence: 99%
“…Incarceration provides an opportunity (however regrettable) to identify undiagnosed and untreated mental health and substance use needs and connect people to resources. The transition period from custody to community is a high-risk time for adverse outcomes, including mortality and return to custody (Butler et al, 2023;Kouyoumdjian et al, 2016). given the short length of stay in provincial correctional settings, case management, thorough discharge planning, and linkage to community services should be prioritized.…”
Section: Discussionmentioning
confidence: 99%